The impact of the dimensions of social performance on firm risk - Bouslah, Kais; Kryzanowski, Lawrence; M’Zali, Bouchra (Journal of Banking & Finance, 2013)
This paper examines the impact of the individual dimensions of social performance (SP) on firm risk (total and idiosyncratic) using 16,599 firm-year observations over the period 1991–2007. We find that firm risk for S&P500 members is positively affected by Employee, Diversity, and Corporate Governance concerns. On the other hand, Community (Diversity) strengths negatively (positively) affect their risk. As to non-S&P500 members, firm risk is positively affected by Employee concerns and Diversity strengths. However, firm risk of non-S&P500 members is negatively affected by Environment strengths. The direction of causation between firm risk and SP depends on the dimension examined.